Incidence of Gender in the Teacher’s Digital Competence: A Meta-Analysis Study - Rini, Indah Mustika; Sarifah, Iva; riyadi (Jurnal Teknologi Pendidikan, 2024)
Abstract: These research aims to analyse and compare (differ) the level of teacher’s Digital Competence across gender. A meta-analysis systematically examined the related studies in Google Scholar database and highlight the methodological and effect size issues found within the literature. A total of 6 eligible studies were included in the final analysis, including 430.406 teachers. The forest plot, funnel plot, Rank Correlation and Regression Method are used to summarize and visualize the results of multiple studies and conduct subgroup analyses. The finding revealed moderate and positive impact size (random effects model) of r = 0.23 with a 95% confidence interval with the digital competency of male teachers is 23% higher than that of female ones. Keywords: Digital Competence, gender, meta-analysis, effect size